Konstruksi Pemberitaan Kompas.com terhadap Kasus Pornografi Dea Onlyfans - I Komang Agus Widiantara (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Almost all mass media, especially online media in Indonesia, take advantage of eroticism or pornography news as one of the main attractions for reporting. Kompas.com is among those who consistently report on the immoral video scandal of Dea Onlyfans in the period March-April 2022. The purpose of this study is to describe the pattern and construction of the news that was carried out by kompas.com in the pornographic case of Dea Onlyfans which various parties have highlighted. Kompas.com's spirit of quality journalism doesn't seem to be in line with kompas.com's exploitation of exaggerating or framing immoral news compared to other important news in the midst of the post-Covid-19 crisis, until the government's policies in Indonesia have been criticized. This study uses a qualitative method with a constructive approach. Researchers analyzed the presentation of the results of news construction using the framing model of Zhongdan Pan and Gerald M. Kosicki. As for the results of the analysis, namely Syntax, kompas.com relied on sensational and chronological news titles in exploiting immoral news; The script, Kompas.com is able to build interesting stories and make readers